Surface plasmon resonance (SPR) biosensors for food allergen detection in food matrices - Zhou, Jinru; Qi, Qinqin; Wang, Chong; Qian, Yifan; Liu, Guangming; Wang, Yanbo; Fu, Linglin (Biosensors & bioelectronics, 2019)
Food allergies are recognized as a growing public health concern, with an estimated 3% of adults and 6-8% of children affected by food allergy disorders. Hence, food allergen detection, labeling, and management have become significant priorities within the food industry, and there is an urgent requirement for reliable, sensitive, and user-friendly technologies to trace food allergens in food products. In this critical review, we provide a comprehensive overview of the principles and applications of surface plasmon resonance (SPR) biosensors in the identification and quantification of food allergens (milk, egg, peanut, and seafood), including fiber-optic surface plasmon resonance (FOSPR), surface plasmon resonance imaging (SPRI), localized surface plasmon resonance (LSPR), and transmission surface plasmon resonance (TSPR). Moreover, the characteristics and fitness-for-purpose of each reviewed SPR biosensor is discussed, and the potential of newly developed SPR biosensors for multi-allergen real-time detection in a complex food system is highlighted. Such SPR biosensors are also required to facilitate the reliable, high-throughput, and real-time detection of food allergens by the food control industry and food safety control officials to easily monitor cross-contamination during food processing. [Display omitted] •Four types of surface plasmon resonance (SPR) biosensors are reviewed.•Applications of SPR biosensors for food allergens detection are introduced.•Potential applications of SPR biosensors are discussed for allergen detection.